PERAN KEPERCAYAAN DALAM MEMEDIASI PENGARUH DIGITAL MARKETING DAN LIVE STREAMING TERHADAP MINAT BELI - Faiza, Nur; Rachman, Riza (Growth, 2024)
Consumer interest in online shopping has become increasingly crucial. The accessibility and security offered by e-commerce platforms have attracted consumer interest. The objective of this research is to examine the role of trust in mediating the influence of digital marketing and live streaming on purchase intention. The research employs a quantitative method by surveying 140 TiktokShop users in Situbondo. Data analysis utilizes Partial Least Square (PLS) conducted through the SmartPLS program. The results indicate that digital marketing has a positive and significant influence on trust, live streaming has a positive and significant influence on trust, digital marketing has a positive and significant influence on purchase intention, live streaming has a positive and significant influence on purchase intention, trust has a positive and significant influence on purchase intention, and trust as an intervening variable contributes to mediating the relationship between digital marketing and purchase intention. Furthermore, trust as an intervening variable also contributes to mediating the relationship between live streaming and consumer purchase intention.